Building an Integrated System for the Management of Scientific Nature Events through Open Source Software Integration - Serrão, C.; Gamito, M. (Advances in Information Systems and Technologies, 2013)
This article presents the development of a specific software system through the integration of several open source applications. This integration makes use of several synchronous Enterprise Application Integration (EAI) techniques that were grouped as a way to keep the applications the most independent possible. The integration process was conducted directly on the source code of the applications, making usage of open source applications as an asset. This article presents and approach that allows the development of new software solutions through the integration of several open source applications.